Tungsten erosion by impurities and redeposition: focus on the magnetised sheath. (6th February 2017) - Mellet, N; Gunn, J P; Pégourié, B; Marandet, Y; Martin, C; Roubin, P
Abstract: The effect of the magnetised sheath on the gross erosion and redeposition of tungsten is examined with an insight on impurity impact energy and angle. A complete treatment of the impact energy is performed leading to a scaling that differs from the usual 2 k B T i + 3 Zk B T e formula. It is found that even if the energy distribution at the sheath entrance strongly differs from this approximation, the discrepancy remains under 20% for the impact energy. The average impact angle of a set of impurities is calculated. The difference between models with and without sheath electric field depends strongly on the charge state and mass of the impurity considered. This can lead, for example in the case of gross sputtering due to impinging W 12 +, to an underestimation of 3–4 times at T e = 25 eV for very grazing angles. Scalings for high and low density cases, which correspond for fusion relevant magnetic fields ( B = 2 − 8 T ) to n e > 10 20 m −3 and n e < 10 15 m −3, respectively, are deduced and provide a good estimation of the average impact angle of all impurities. Finally the magnetised sheath is shown to have an effect on the redeposition through two contributions: it increases the prompt redeposition contribution to the total redeposition and constitutes a potential barrier for the ions leaving the surface. A discussion is provided about the optimal width of the simulation domain to capture these effects.